Eficiência de uso do nitrogênio por gramíneas em função do modo de aplicação de dejetos suínos no solo e do uso de inibidor de nitrificação - Gonzatto, Rogerio (2016)
The effect of pig slurry (PS) injection into the soil and nitrification inhibitor use such as dicyandiamide (DCD) on gaseous N losses to the atmosphere is better documented than the effect of these practices on nitrogen use efficiency (NUE) and crop productivity. The aim of this work was to evaluate how the PS application method (shallow injection vs surface broadcasting) in no-till (NT) and DCD addition to PS affects the recovery of PS ammonium N (NH4-N) in the soil-plant system, NUE and productivity in a succession of grasses (corn/oat-wheat). Two studies were performed in the field at Universidade Federal de Santa Maria, in a Typic Paleudult. The experimental design was in randomized blocks with four repetitions of the following treatments: surface broadcast of pig slurry (PSs), PSs + DCD, injected PS (PSi), PSi + DCD, and control and surface application of mineral (NPK). Studies began in December 2011, with the first one finalized in June 2013 and the second in December 2015. In the first study, the PS ammonium fraction (NH4+-N) was 15N enriched to follow the fate of this fraction in the soil-plant system. Compared with the broadcast application, PS injection into the soil was more effective when followed by low soil moisture conditions, increasing in 22 kg N ha-1 the recovery of PS NH4+-N in corn. However, the DCD was more efficient in situations with higher soil moisture, increasing in 24 kg N ha-1 the recovery of NH4+-N in corn. In addition, PS injection efficiency was improved when combined with DCD, increasing in 21% NH4+-N retention in the plant-soil system. In the second study, PS injection also increased the apparent recovery of N (21%), agronomic efficiency of N (33%) and crop productivity (10%) compared to surface application. DCD use did not have significant effect on all crops, although, on the other hand, its use in wheat/2013 improved the evaluated attributes. The best performance of crops with PS injection as NUE is related mainly to the efficiency of this practice to reduce N losses by ammonia (NH3) volatilization, ensuring greater N availability for uptake by crops. The DCD, nevertheless, seems to be more effective when its application is followed by periods of high humidity, which favour N losses by denitrification or nitrate leaching (NO3-), and/or low temperatures that increase the longevity of the product in the soil. In conclusion, these results indicated that PS injection into the soil in NT is a promising alternative management for PS surface broadcasting, while the use of DCD requires further studies evaluating its effect on NUE by crops varying the soil and local weather conditions.